2001
DOI: 10.1021/jo0013148
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Catalyzed CC Bond Cleavage by Molecular Oxygen Promoted by a Thiyl Radical

Abstract: Olefin oxidation with molecular oxygen, promoted by a transition metal catalyst and a thiophenol, involved C=C bond cleavage into the corresponding carbonyl derivatives. This new reaction proceeds under one atmosphere of oxygen, at room temperature, in the presence of an excess of thiophenol and a catalyst such as MnL(2) 3a or VClL(2) 3c. It was applied to aromatic and aliphatic olefins, as well as to functionalized or unfunctionalized acyclic compounds, providing the corresponding ketones and aldehydes in up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(29 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…Corey [20] had previously reported 22 in 80 % ee (87 % yield) and MacMillan [18] obtained 24 in 85 % ee (79 % yield) so here the Ru catalyst system outperforms the literature catalysts in terms of ee though the yields are lower. The absolute stereochemistry of the compounds in Table 2 have been reported previously (except 21); 23 has been prepared from (À)-limonene, [32] 22 was assigned by Corey [20] by analogy to 10 and MacMillan [18] prepared an authentic sample of 24 from the corresponding chiral aldehyde.…”
Section: Diels-alder Reactions With Acyclic Dienesmentioning
confidence: 99%
“…Corey [20] had previously reported 22 in 80 % ee (87 % yield) and MacMillan [18] obtained 24 in 85 % ee (79 % yield) so here the Ru catalyst system outperforms the literature catalysts in terms of ee though the yields are lower. The absolute stereochemistry of the compounds in Table 2 have been reported previously (except 21); 23 has been prepared from (À)-limonene, [32] 22 was assigned by Corey [20] by analogy to 10 and MacMillan [18] prepared an authentic sample of 24 from the corresponding chiral aldehyde.…”
Section: Diels-alder Reactions With Acyclic Dienesmentioning
confidence: 99%
“…Recently, photochemical OCO methods have been reported with the photon as a traceless reagent and a green source of energy. [8][9][10][11][12] In general, these methods required UV-light, or catalysts that are toxic [8] or metal-based, [9] or a demandingly oxidative photoredox catalyst to be SET-reduced by the olefin. [10][11][12] Alternatively, it would be attractive to seek a nonmetal photocatalyst that functions via a non-redox/sensitization mechanism, and preferably with a reduced cost than most photocatalysts.…”
mentioning
confidence: 99%
“…However, high selectivity of benzaldehyde has been reported by few authors [25][26][27][28] with certain demerits. Baucherel et al [25] reported the unexpected high selectivity towards the C@C cleavage of olefins in the presence of molecular oxygen with Mn-salen with thionyl radical promoter, but the used catalyst is homogeneous, and in addition, mixing of thionyl radical and H 3 PO 4 are the drawbacks of this system. As a safety alternative to ozonolysis, Miyamoto et al [58] developed an efficient method for C@C bond cleavage with high yields of aldehydes, using a combination of iodosylbenzene and HBF 4 in the presence of water, but this method is also homogeneous in nature.…”
Section: Oxidative Cleavage Of C@c Bond Of Olefinsmentioning
confidence: 99%
“…Over-oxidation of aldehyde to the corresponding acid as side-reaction is in most cases unavoidable. Despite mild and selective oxidation methods gaining increased importance, only few novel or improved methods for cleavage of C@C bond of alkenes are available [25][26][27][28]. Therefore, the development of inexpensive, selective, safe and environmentally friendly procedure for the cleavage of C@C bonds is highly desirable.…”
Section: Introductionmentioning
confidence: 99%